2021
DOI: 10.1186/s12866-021-02232-z
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Clonality of drug-resistant tuberculosis in South Africa

Abstract: Background Studies have shown that drug-resistant tuberculosis (DR-TB) in South Africa (SA) is clonal and is caused mostly by transmission. Identifying transmission chains is important in controlling DR-TB. This study reports on the sentinel molecular surveillance data of Rifampicin-Resistant (RR) TB in SA, aiming to describe the RR-TB strain population and the estimated transmission of RR-TB cases. Method RR-TB isolates collected between 2014 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 35 publications
6
10
0
Order By: Relevance
“…A comparison of lineages among all clinics/hospitals in this study shows that the Beijing family was the commonest genotype found in all the hospitals/clinics, with HCF 2, HCF 3, HCF 5, and HCF 6 having a higher proportion of Beijing isolates. The Beijing family is known to be more transmissible than other families and more prevalent in Eastern Cape and Western Cape provinces, which are neighbors [ 42 , 43 ]; this confirms its high prevalence in this study (42%). This family has been detected in studies reported from other parts of South Africa, including Limpopo, the Western Cape, and Mpumalanga [ 43 , 44 ].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…A comparison of lineages among all clinics/hospitals in this study shows that the Beijing family was the commonest genotype found in all the hospitals/clinics, with HCF 2, HCF 3, HCF 5, and HCF 6 having a higher proportion of Beijing isolates. The Beijing family is known to be more transmissible than other families and more prevalent in Eastern Cape and Western Cape provinces, which are neighbors [ 42 , 43 ]; this confirms its high prevalence in this study (42%). This family has been detected in studies reported from other parts of South Africa, including Limpopo, the Western Cape, and Mpumalanga [ 43 , 44 ].…”
Section: Discussionsupporting
confidence: 84%
“…The Beijing family is known to be more transmissible than other families and more prevalent in Eastern Cape and Western Cape provinces, which are neighbors [ 42 , 43 ]; this confirms its high prevalence in this study (42%). This family has been detected in studies reported from other parts of South Africa, including Limpopo, the Western Cape, and Mpumalanga [ 43 , 44 ]. Nelson et al [ 45 ] reported that human movement between rural and urban areas in search of employment in South Africa is common and serves as a bridge for transporting pathogens across long distances.…”
Section: Discussionsupporting
confidence: 84%
“…A comparison of lineages among all clinics/ hospitals in the study shows that the Beijing family was the only genotype found in all the hospitals/ clinics, with HCF 2, HCF 3, HCF 5 and HCF 6 having the highest number of Beijing isolates. The Beijing family is known to be more transmissible than other families and more prevalent in Eastern Cape and Western Cape Provinces which are neighbors [48,49] this confirms its high prevalence in this study (42%). This family has been detected in studies reported from other parts of South Africa including Limpopo, Western Cape and Mpumalanga [49,50].…”
Section: Discussionsupporting
confidence: 84%
“…The Beijing family is known to be more transmissible than other families and more prevalent in Eastern Cape and Western Cape Provinces which are neighbors [48,49] this confirms its high prevalence in this study (42%). This family has been detected in studies reported from other parts of South Africa including Limpopo, Western Cape and Mpumalanga [49,50]. Nelson et al [51] reported that human movement between rural and urban areas in search of employment in South Africa is common and serves as a bridge for transporting pathogen across long distances.…”
Section: Discussionsupporting
confidence: 84%
“…Second, we could not assess the BDQ MIC for four of the 36 unique variants as some samples failed to grow. Third, reflecting the epidemiology of Mtb in South Africa (41), isolates of lineage 5, 6 or 7 were absent and isolates of lineages 1 and 3 were rare. Lastly, CFZ exposure, which can result in BDQ cross-resistance through mutations in the Rv0678 gene, was not considered because data on CFZ exposure status was not available (42).…”
Section: Discussionmentioning
confidence: 99%